SYMPATHETIC HYPERACTIVITY IN CHRONIC KIDNEY DISEASE PATIENTS: FROM PATHOGENESIS TO TREATMENT - N. Stepanova (Ukrainian Journal of Nephrology and Dialysis, 2017)
Sympathetic nervous system plays a crucial role in the development of cardiovascular complications in chronic kidney disease (CKD) patients. The aim of this review is to summarize up-to-date knowledge of the sympathetic hyperactivity in the pathogenesis of CKD, its clinical relevance, and as the options of current treatment.